Centennial-Scale Temperature Change During the Common Era Revealed by Quantitative Temperature Reconstructions on the Tibetan Plateau - Li, Xiumei; Zhang, Yong; Wang, Mingda; Yan, Junhui; Fan, Baowei; Xing, Wei; He, Yue; Hou, Juzhi (Frontiers in Earth Science, 2020)
Quantitative palaeotemperature reconstruction is crucial for understanding the evolution of Earth’s climate and reducing uncertainty in future climate predictions. Clarifying the temperature change over the Tibetan Plateau (TP) during the Common Era is critical because it plays a vital role in the prediction of cryosphere changes in such regions under a future warming climate. In this paper, we report a comprehensive synthesis of currently available quantitative temperature records to refine the temperature history of the TP during the Common Era. To date, Common Era quantitative temperature reconstructions are sparse and mainly concentrated in the northeastern TP. Considering seasonal bias of the available quantitative temperature reconstructions, three different composite temperature records for TP were derived, namely the “Standardization” composite, the “Mean annual air temperature anomaly” composite, and the “Mean summer temperature anomaly” composite individually. All the integrated temperature series reveal the Medieval Climate Anomaly and the Little Ice Age, but the start and end timings of these multi-centennial-scale periods and their temperature amplitudes differ. There is strong seasonality in temperature variations on this high plateau, and the 20th century warming was characterized by rapid winter temperature increases, while summer temperatures displayed weak variations. Spatial analysis suggests a relatively consistent signal marking a warm TP during 600–1400 CE and a cold plateau during 1400–1900 CE. Large-scale trends in temperature history for the TP resemble those for China and the Northern Hemisphere. Many factors, such as seasonality of temperature proxies, might lead to uncertainty in the reconstructed series. The results highlight that it is of crucial importance to develop more seasonal temperature reconstructions to improve the reliability of quantitative paleoclimatic reconstructions based on geological records across the TP.